Alkaloids isolated from Tabernaemontana bufalina display xanthine oxidase inhibitory activity. (October 2019) - Shi, Bao-Bao; Chen, Jing; Bao, Mei-Fen; Zeng, Ying; Cai, Xiang-Hai
Abstract: Continued interest in bioactive alkaloids led to the isolation of four undescribed alkaloids along with 74 known ones from the aerial parts of Tabernaemontana bufalina Lour . The structures of the yet undescribed alkaloids were elucidated based on NMR, IR, UV, MS and CD spectroscopic data and X-ray crystal diffraction and, according to the plant source, named as taberhaines A–D (1 –4 ). The known compounds comprised of 66 monoterpenoid indole, three carboline and five isoquinoline alkaloids. Among them, the known apparicine inhibited significantly the activity of xanthine oxidase, which plays an important role for gout, with an IC50 value of 0.65  μ M, compared to the standard drug allopurinol (IC50  = 0.60  μ M). Graphical abstract: Image 1 Highlights: Four undescribed alkaloids together with 74 known ones were isolated from Tabernaemontana bufalina. The structures were determined by NMR spectra, CD data and X-ray diffraction. Apparicine exhibited a significant inhibitory activity of xanthine oxidase compared to allopurinol.